FAKTOR PENUNJANG DAN PENGHAMBAT AGRIBISNIS BUAH STROBERI DI KELURAHAN RURUKAN DAN RURUKAN SATU, KECAMATAN TOMOHON TIMUR, KOTA TOMOHON - Riane W. Senewe; Agnes E. Loho; Mex L. Sondakh (AGRI-SOSIOEKONOMI, 2016)
The study aimed to assess factors - supporting and inhibiting factors in Agribusiness Strawberries. This research was conducted in the Village Rurukan and Rurukan One, Sub-district of East Tomohon, Tomohon City. The study lasted for 3 (three) months, from July to September 2016 starting from preparation through research reports. This study uses primary data and secondary data. The samples in this study were all strawberry farmers in Rurukan and Rurukan One, they are 7 strawberries farmers in which five farmers who are still active, while two farmers are no longer planted strawberries, consumers or tourists who visit, and the institution or village. Data analysis method used is descriptive (descriptive analysis), where the study was conducted to examine the factors supporting and inhibiting agribusiness Strawberries. The results showed that the factors - factors supporting and inhibiting the main agribusiness strawberries for subsystem Agriinput, Subsystem Agriproduksi, Subsystems Agriindustri, Subsystems Agriniaga, and Subsystem Agriservis. The detail findings are: (a) subsystems Agriinput main supporting factors are strawberry seeds, fertilizers and labor while the main inhibiting factor is the land, the weather and the capital; (b) subsystem Agriproduksi main supporting factor is the knowledge of farmers on the cultivation of strawberries and strawberry fruit prices, while the limiting factor is the main weather and capital; (c) sub-system Agriindustry main supporting factors are: processing technology, while being the main limiting factor is the capital and processing equipment; (d) subsystem Agricommerce main supporting factor is the market, price of Strawberries and that became the main limiting factor is the capital; (e) Subsystem Agriservice main supporting factors are education, agricultural extension and being the main limiting factor is the information.